(C3H9NI)4AgBiI8: a direct-bandgap layered double perovskite based on a short-chain spacer cation for light absorption. Issue 21 (19th February 2020) - Yao, Yunpeng; Kou, Bo; Peng, Yu; Wu, Zhenyue; Li, Lina; Wang, Sasa; Zhang, Xinyuan; Liu, Xitao; Luo, Junhua
Abstract : A new iodide layered double perovskite (C3 H9 NI)4 AgBiI8 (IPAB) has been developed based on a short-chain spacer cation, which is the first homologous compound in iodide double perovskites that adopt the Ruddlesden–Popper structure type. Abstract : A new iodide layered double perovskite (C3 H9 NI)4 AgBiI8 (IPAB) has been developed based on a short-chain spacer cation, which is the first homologous compound in iodide double perovskites that adopt the Ruddlesden–Popper structure type. Importantly, IPAB is a promising environmentally friendly alternative to the recently rapidly progressing lead halide semiconductors owing to its narrow direct-bandgap of 1.87 eV and excellent stability.